2020
DOI: 10.15252/emmm.202012519
|View full text |Cite
|
Sign up to set email alerts
|

Striatal infusion of cholesterol promotes dose‐dependent behavioral benefits and exerts disease‐modifying effects in Huntington's disease mice

Abstract: A variety of pathophysiological mechanisms are implicated in Huntington's disease (HD). Among them, reduced cholesterol biosynthesis has been detected in the HD mouse brain from presymptomatic stages, leading to diminished cholesterol synthesis, particularly in the striatum. In addition, systemic injection of cholesterol-loaded brain-permeable nanoparticles ameliorates synaptic and cognitive function in a transgenic mouse model of HD. To identify an appropriate treatment regimen and gain mechanistic insights i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
56
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(64 citation statements)
references
References 83 publications
5
56
2
Order By: Relevance
“…We have recently demonstrated that a therapeutically relevant dose of cholesterol delivered to the striatum through osmotic mini-pumps indirectly stimulated endogenous cholesterol synthesis, leading to the reversal of both motor and cognitive abnormalities in HD mice [19]. In contrast, lower doses delivered to the striatum through osmotic mini-pumps [19] or to the brain via PLGA-g7-NPs-chol [13] led to a complete rescue of cognitive decline without significant change in endogenous brain cholesterol biosynthesis or in motor performance.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have recently demonstrated that a therapeutically relevant dose of cholesterol delivered to the striatum through osmotic mini-pumps indirectly stimulated endogenous cholesterol synthesis, leading to the reversal of both motor and cognitive abnormalities in HD mice [19]. In contrast, lower doses delivered to the striatum through osmotic mini-pumps [19] or to the brain via PLGA-g7-NPs-chol [13] led to a complete rescue of cognitive decline without significant change in endogenous brain cholesterol biosynthesis or in motor performance.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies pointed out the benefits of strategies aimed at delivering cholesterol to the HD brain [13, 19], but defining the dose of cholesterol that reaches the brain is critical to a complete understanding of the power and limits of the approach. With the aim of developing a new and non-invasive strategy closer to clinical application, hybrid-g7-NPs-chol were produced with improved chemical and physical properties and increased cholesterol content [21].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations